The moderating eﬀect of risk management committee on board diversity and firm value - Rina Rosia,; Ayu Dwi Ria Hayuti, (Indonesian Journal of Islamic Economics Research, 2024)
This paper attempts to deepen a better understanding of role risk management committee in mediate board diversity to firm value. Board diversity is proxied with gender of the board of directors, age of the board of directors, and setting behind board of director education. The firm value proxied with ratio Tobin's Q and the risk committee be measured with variable dummy. Type study This is study quantitative with population that is firm manufacturers registered with ISSI for the 2020-2022 period, total sample a total of 69 samples from 23 company data with method purposive sampling. Method data analysis using technique panel data regression with SPSS software version 25. Research results show age of the board of directors influential positive significant to firm value, meanwhile board of director gender and setting behind education no influential to firm value. Variable risk management committee no capable moderate influence gender of the board of directors, age of the board of directors, and setting behind education of the board of directors to firm value.